Use of prostate-specific antigen testing in Medicare beneficiaries: Association with previous evaluation. Issue 2 (1st July 2017) - Cooper, Gregory S.; Kou, Tzuyung Doug; Schluchter, Mark D.; Dor, Avi; Koroukian, Siran M.; Kim, Simon P.
Abstract : Objective: Determine uptake of prostate-specific antigen (PSA) testing in Medicare beneficiaries according to previous receipt of PSA testing. Methods: A 5% random sample of men aged 67 years or older without a previous diagnosis of prostate cancer was identified through 2009–2012 Medicare claims. We measured the annualized frequency of PSA screening among men due for PSA testing, stratified by PSA testing use in the previous 2 years, and clustered by ordering provider. Results: Throughout the study period, PSA testing use was consistently higher for men with previous screening than for men without previous screening. For men without previous screening, there was a decline in testing that was most pronounced in 2012. Compared with 2009, the corresponding odds ratios were 0.98 [95% confidence interval (CI) (0.96–1.00)] in 2010, 0.94 [95% CI (0.92–0.95)] in 2011, and 0.66 [95% CI (0.65–0.68)] in 2012. In contrast, for men with previous screening, PSA testing frequency was stable from 2009 to 2011, and declined to a lesser extent in 2012 [odds ratio 0.80, 95% CI (0.79–0.81)]. Conclusion: Receipt of PSA testing is highly dependent on whether an individual was tested in the recent past. In previously unscreened men, the largest decrease occurred in 2012, which may reflect in part the publication of US Preventive Services Task Force guidelines, but there was much less impact among men already being screened.